Theatrical design and production : an introduction to scenic design and construction, lighting, sound, costume, and makeup - Gillette, J. Michael; Dionne, Rich (McGraw-Hill Education, 2020)
"First courses in the world of theatrical design and production, like the art they introduce, come in a bewildering array of shapes, sizes, textures, and colors. Some students receive their introduction to this subject area in a general overview course that covers the design and production elements of scenery, costumes, lighting, and sound in a single semester. Other students may enjoy the luxury of an entire year in which to discuss the same material. Still others may take individual courses that specialize in the theory and craft of the separate areas that comprise the field of theatrical design and technical production. The course content is very flexible indeed. This 8th edition of Theatrical Design and Production has been extensively revised. Every chapter has had minor--and in some cases major--revisions to bring the information it offers in line with current standards and practices"--